Inner Tube of AL-Diwanyia Tyre Based on Natural Rubber Blends - Motar, M. .A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Most tubes are made from butyl rubbers, but certain types, such as giant tubes, are based on natural rubber because very high green strength is required when handling the uncured compound. By using blends of natural rubber (NR) and brominated butyl rubber (BIIR), it is possible to maintain high green strength in the uncured compound and improve impermeability and heat resistance of the cured tube. The best formulations are obtained in the presence of 50 phr of (BIIR) to achieve desired mechanical properties. Improved impermeability was obtained by using 50 and 75 phr of (BIIR) rubber in compounds. Blending of brominated butyl rubber (BIIR) with natural rubber (NR) enhances air retention with acceptable sacrifices in green strength. When using blends of natural rubber and brominated butyl rubber it is necessary to reduce the sulfur as the brominated butyl rubber (BIIR) content is increased.